Happy like soccer - Boelts, Maribeth, 1964-; Castillo, Lauren (Somerville, Mass. : Candlewick Press, 2012)
For soccer games Sierra rides a bus out of the city to fields that are nicer than the "lot" in her neighborhood, but so her auntie can be at her last game, she asks Coach Marco if the team might play in her neighborhood on a day her aunt does not work.
Keywords: Soccer -- Fiction; Aunts -- Fiction; Problem solving -- Fiction; Social classes -- Fiction